Qualitative ergonomics/human factors research in health care: Current state and future directions. (July 2017) - Valdez, Rupa Sheth; McGuire, Kerry Margaret; Rivera, A. Joy
Abstract: The objective of this systematic review was to understand the current state of Ergonomics/Human Factors (E/HF) qualitative research in health care and to draw implications for future efforts. This systematic review identified 98 qualitative research papers published between January 2005 and August 2015 in the seven journals endorsed by the International Ergonomics Association with an impact factor over 1.0. The majority of the studies were conducted in hospitals and outpatient clinics, were focused on the work of formal health care professionals, and were classified as cognitive or organizational ergonomics. Interviews, focus groups, and observations were the most prevalent forms of data collection. Triangulation and data archiving were the dominant approaches to ensuring rigor. Few studies employed a formal approach to qualitative inquiry. Significant opportunities remain to enhance the use of qualitative research to advance systems thinking within health care. Highlights: 98 qualitative health care papers were published in top E/HF journals (2005–2015). Most research focused on the work of formal health care professionals. Dominant approaches to ensuring rigor included triangulation and data archiving. Only a handful of studies employed a formal qualitative research approach.